Acute disseminated encephalomyelitis presenting as fever of unknown origin: case report - Di Costanzo Margherita; Camarca Maria; Colella Maria; Buttaro Giuseppe; Elefante Andrea; Canani Roberto (BMC, 2011)
Abstract Background Fever of unknown origin (FUO) can be defined as a body temperature higher than 38.3°C on several occasions over more than 3 weeks, the diagnosis of which remains uncertain after 1 week of evaluation. Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disease of the central nervous system with a wide range of clinical manifestations. The highest incidence of ADEM is observed during childhood and it usually occurs following a viral or bacterial infection or, more rarely, following a vaccination, or without a preceding cause. Case presentation Here, we describe an atypical case of ADEM that initially manifested as several weeks of FUO in a fifteen years old boy. Conclusions This case report suggests a new possible syndromic association between ADEM and FUO, which should be considered in the clinical examination of patients with FUO, especially in the presence of also modest neurologic or neuropsychiatric symptoms.